Neural Tissue Engineering: Human Neural Tissues from Neural Stem Cells Using Conductive Biogel and Printed Polymer Microelectrode Arrays for 3D Electrical Stimulation (Adv. Healthcare Mater. 15/2019). Issue 15 (8th August 2019) - Tomaskovic‐Crook, Eva; Zhang, Peikai; Ahtiainen, Annika; Kaisvuo, Heidi; Lee, Chong‐Yong; Beirne, Stephen; Aqrawe, Zaid; Svirskis, Darren; Hyttinen, Jari; Wallace, Gordon G.; Travas‐Sejdic, Jadranka; Crook, Jeremy M.
Abstract : In article number 1900425 Jadranka Travas‐Sejdic, Jeremy M. Crook, and co‐workers, describe development and maturation of human neural tissues with enhanced function and increased response to drug‐induced disinhibition by 3D electrical stimulation using printed pillar microelectrode arrays interfaced with an electrically conductive human neural stem cell‐laden biogel. The cover artwork portrays the work in the brave‐new‐world of neural tissue engineering, brain modelling, and electroceuticals.